A combined experimental, Hirshfeld surface analysis, and theoretical study on fac-[tri(azido)(tris(2-pyridyl)amine)iron(III)]. (15th March 2023) - Setifi, Zouaoui; Cubillán, Néstor; Glidewell, Christopher; Gil, Diego M.; Torabi, Elham; Morales-Toyo, Miguel; Dege, Necmi; Setifi, Fatima; Mirzaei, Masoud
Graphical abstract: An interesting N 3– ···N 3– interaction has been found in the title complex and related to n→π* donation of the anions arranged in a cage structure. Abstract: A novel Fe(III) complex with the general formula [Fe(tpa)(N3 )3 ] (1) (tpa = tris(2-pyridyl)amine), has been prepared by solvothermal synthesis and characterized by standard spectroscopic and analytical methods to determine its composition. Crystal structure analysis at 170 K shows that the tris(2-pyridyl)amine ligand is coordinated in tridentate fashion via the pyridyl N atoms and the complex as a whole has approximate threefold rotational symmetry: the Fe–N distances indicate that the metal centre adopts a low-spin configuration at 170 K. A combination of two C-H··· N hydrogen bonds and two azido··· π(pyridyl) interactions link the molecules into a continuous three-dimensional array. An analysis of the complex total energy evaluated the preference of the high-, intermediate- and low-spin complexes. DFT calculations showed that the high-spin complex is the least energetic of the three possible spin states. The Quantum Theory of Atoms In Molecules (QTAIM), Reduced Density Gradient (RDG), and Natural Bond Orbitals (NBO) analysis showed an azido··· azido interactions cooperatively assisted by weak hydrogen bonds and lone-pair··· π interactions between N3 – and the pyridine fragment from the tris(2-pyridyl)amine ligand. The amine and N3 – arrange to bear a caged anion. The azido··· azido interaction nature can be related to the donation from the N lone-pair to the π* of the opposite anion.